2021
DOI: 10.3390/children8100925
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ Online Pornography Exposure and Its Relationship to Sociodemographic and Psychopathological Correlates: A Cross-Sectional Study in Six European Countries

Abstract: The aim of the study was to assess the prevalence of online exposure to pornography in European adolescents and its relationship to sociodemographic and psychopathological correlates. A cross-sectional school-based survey of 10,930 adolescents (5211 males/5719 females), aged 14–17 years old (mean age 15.8 ± 0.7) was carried out in six European countries (Greece, Spain, Poland, Romania, the Netherlands, and Iceland). Anonymous self-completed questionnaires covered exposure to pornography, internet use and dysfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 74 publications
0
18
1
4
Order By: Relevance
“…Exposure to sexually explicit materials in our study varied from 32 to 65%, and on average, 48% of adolescents reported that they had seen some sexually explicit materials in the past year, online or offline. This prevalence is slightly lower than that reported in previous research (see, for example, Andrie et al, 2021 who asked adolescents about sexually explicit media and Donevan et al, 2021 who inquired about watching pornography). One possible explanation for the lower rates in our sample might be that the mean age of our sample was 14.04 years old, whereas both of the other studies sampled high schoolers, and exposure to sexually explicit materials in known to increase with age (Ševčíková et al, 2014 ; Perry & Heyward, 2017 ; Ma et al, 2017a ).…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Exposure to sexually explicit materials in our study varied from 32 to 65%, and on average, 48% of adolescents reported that they had seen some sexually explicit materials in the past year, online or offline. This prevalence is slightly lower than that reported in previous research (see, for example, Andrie et al, 2021 who asked adolescents about sexually explicit media and Donevan et al, 2021 who inquired about watching pornography). One possible explanation for the lower rates in our sample might be that the mean age of our sample was 14.04 years old, whereas both of the other studies sampled high schoolers, and exposure to sexually explicit materials in known to increase with age (Ševčíková et al, 2014 ; Perry & Heyward, 2017 ; Ma et al, 2017a ).…”
Section: Discussioncontrasting
confidence: 59%
“…As adolescents explore their sexuality, it is normative for them to seek out sexually explicit materials offline (Steinberg et al, 2019 ) as well as online (Subrahmanyam & Šmahel, 2011 ). Across Europe, there is variability in adolescents’ reported exposure to sexually explicit materials as a function of both country and gender (Andrie et al, 2021 ; Donevan et al, 2022 ; Ševčíková & Daneback, 2014 ; Šmahel et al, 2020 ). Their reasons for seeking sexually explicit materials are similarly varied and include wanting to be sexually aroused, satisfying curiosity about sex, being in a romantic relationship, wanting to learn more about it, and for some, a type of friendly socialization (Löfgren-Mårtenson & Månsson, 2010 ; Ševčíková & Daneback, 2014 ; Smith, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some topics, such as young people’s use of online pornography and online gambling, were not included in the GPIs despite indication that these online activities are relevant to young people’s mental wellbeing [ 20 , 21 ]. Such activities are patterned by characteristics including sex and the underrepresentation of male participants in our panel may have led to an underestimation of importance.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, orientated by the Developmental Psychopathology framework, we tried to raise the argument that Internet use in young subjects poses a number of risks, regardless of how often and how long the Web is used [12]. In the case of pornography consumption, the same pattern appears to delineate (in our opinion), with several studies reporting pornography use by young adolescents as a cultural/social phenomenon, almost ignoring possible risks, if not in the case of excessive use [13].…”
Section: What Is Happening Today?mentioning
confidence: 99%